2007
DOI: 10.2471/blt.06.033746
|View full text |Cite
|
Sign up to set email alerts
|

A balanced scorecard for health services in Afghanistan

Abstract: The Ministry of Public Health (MOPH) in Afghanistan has developed a balanced scorecard (BSC) to regularly monitor the progress of its strategy to deliver a basic package of health services. Although frequently used in other health-care settings, this represents the first time that the BSC has been employed in a developing country. The BSC was designed via a collaborative process focusing on translating the vision and mission of the MOPH into 29 core indicators and benchmarks representing six different domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
172
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(183 citation statements)
references
References 5 publications
1
172
2
1
Order By: Relevance
“…Their further conclusion that "Strategies for scaling up IMCI and other child-survival interventions might rely on health workers with shorter duration of pre-service training being deployed to underserved areas" was similar to the perspective of MoPH after 2008 to expand IMCI training to nurses and midwives in an attempt to increase availability of trained health workers in areas where nurses or midwives were the highest level of trained health worker. The fact that non-physicians performed less well in the counselling score is surprising in light of the literature and additional research would be necessary to elucidate this further (21). Previous studies in Afghanistan have also identified that female health workers performed better in counselling and providing quality care to children, findings not substantiated by this evaluation (10,19).…”
Section: Direct Observation Integrated Management Of Childhood Illnescontrasting
confidence: 40%
See 2 more Smart Citations
“…Their further conclusion that "Strategies for scaling up IMCI and other child-survival interventions might rely on health workers with shorter duration of pre-service training being deployed to underserved areas" was similar to the perspective of MoPH after 2008 to expand IMCI training to nurses and midwives in an attempt to increase availability of trained health workers in areas where nurses or midwives were the highest level of trained health worker. The fact that non-physicians performed less well in the counselling score is surprising in light of the literature and additional research would be necessary to elucidate this further (21). Previous studies in Afghanistan have also identified that female health workers performed better in counselling and providing quality care to children, findings not substantiated by this evaluation (10,19).…”
Section: Direct Observation Integrated Management Of Childhood Illnescontrasting
confidence: 40%
“…In Rowe et al 's review, however, the three studies that directly compared post-training performance between short and standard IMCI courses also concluded that there was no significance difference in post-training performance between groups (8,16). Our second finding -physicians trained in the 7-Day course did slightly better than physicians trained in the 11-Day course in providing three reasons to return to the health centre and in counselling about breastfeeding, increased liquid intake and the importance of follow-up -is remarkable because, poor counselling has been identified as typical of physicians (21). We highlight, however, that the statistical power in this study was insufficient to demonstrate a difference and that pursuing this line of inquiry requires a larger study.…”
Section: Direct Observation Integrated Management Of Childhood Illnesmentioning
confidence: 94%
See 1 more Smart Citation
“…18,19 Two rounds of assessment have been completed since 2004. The exercise is aimed at monitoring and evaluating the delivery of basic health-care services in the 34 provinces covered by national and international NGOs and through internal contracts with the provincial tiers within the public health ministry (via the strengthening mechanism).…”
Section: Monitoring and Evaluationmentioning
confidence: 99%
“…These types of assessments can be used for periodic review, evaluation, and course corrections, often integrating the assessments into a regular planning and budgeting cycle, so that problems can be identified and addressed through re-prioritization of efforts and re- 17,18 The trigger to take this approach has ranged from formation of a new government and new national health policy, to concerns from civil society organizations concerning poor quality or inequality in the performance of the national health system, or a planned evaluation of health reforms.…”
Section: To Translate Health Reforms Into Meaningful Tracking and Evamentioning
confidence: 99%